On a traditional Karanga song - Lenherr, Joseph (International Library of African Music, 1964)
When collecting traditional music among the Karanga tribes of Southern Rhodesia in 1961 /62,I recorded three versions of the song: Vana vapfumo jena. In 1964 I worked on a preliminary survey of the collected material under the guidance of Dr. Wachsman at Ucla, and I found that this specific piece was recorded by H. Tracey and published in the Sound of Africa Series (AMA TR-82 and 173). Through his kindness yet another version that he had recorded on wax-cylinders in 1929 became available. This study is a comparison of these six versions3. It may give some clues on the development and change within this musical culture.
Keywords: Karanga (African people); Music; Songs; African Music